Conceptual bases for managing the processing and distribution of discrete flows in a multicommodity communication network. Part II. Information technologies for decision support in communication networks - Vasyanin, V.; Trofymchuk, O. (Проблеми керування та інформатики, 2025)
The article discusses methodological approaches to the construction of multicom-modity hierarchical communication networks and identifies the main tasks of pro-cessing and distribution of discrete correspondence flows, which allow to create favorable conditions for reducing material, financial and labor costs in transport systems with further mechanization and automation of production. Розглянуто методологічні підходи до побудови багатопродуктових ієрархічних комунікаційних мереж та визначено задачі обробки та розподілу дискретних потоків кореспонденції, що створюють сприятливі умови для скорочення витрат у транспортних системах з подальшою автоматизацією виробництва.